Dendrimer‐Based Gold Nanostructures for SERS Detection of Pesticides in Water. Issue 13 (14th January 2020) - Fernandes, Tiago; Fateixa, Sara; Nogueira, Helena I. S.; Daniel‐da‐Silva, Ana L.; Trindade, Tito
Abstract : Dendrimers are polymers with well‐defined architectures and tunable chemistry, which make them useful in a number of applications. Herein, the chemistry of poly(amido)amine (PAMAM) dendrimers with different functional groups was explored to produce a variety of plasmonic systems based on Au colloidal nanoparticles. The resulting systems present long‐term colloidal stability and were investigated as sensitive platforms for surface‐enhanced Raman scattering (SERS). The application of these SERS platforms for the detection of water trace pollutants, was explored through the analysis of selected pesticides. Noteworthy, dendrimer coated Au nanoparticles with tunable properties such as size, shape and surface chemistry, were obtained by varying the dendrimer chemical properties. The surface chemistry of PAMAM capped Au colloids was explored in order to produce target selective SERS substrates for pesticide detection, that allowed to reach detection limits down to 10 nm . Abstract : The tree‐like shape of dendrimers delivers superior stabilization effect to anisotropic Au nanoparticles along with the ability to capture analytes of interest by interaction with surface groups or physical entrapment. The resulting plasmonic systems can be used for the in‐situ detection of chemical pesticides through SERS under variable operational conditions.